Investor sentiment and asset returns: the case of Indian stock market. (2018) - Mathur, Sachin; Rastogi, Anupam
According to behavioural finance theory, investor sentiment can lead to extreme mispricing of stocks. In this paper we describe the construction of an investor sentiment index for India, an emerging market, to examine the association between sentiment and stock returns. We test whether the sentiment index predicts long-term returns of the stock market, as well as of stock portfolios formed on the basis of size and value characteristics, over the sample period of 2004 to 2016. The sentiment index fails to predict broad market returns, but is inversely associated with the subsequent year's returns of small low-priced stocks, consistent with constrained arbitrage argument of behavioural finance theory and information uncertainty associated with such stocks.